Interactive Learning to Foster Nationalism Among Junior High School Students: Penguatan Wawasan Kebangsaan Melalui Pembelajaran Interaktif di SMPN 2 Kota Bangun - Saputra, Rio Rizky; Ahmad, Andi; Aurelia, Aisha; Nirmala, Amanda; Hasanah, Auliatul; Nikmah, Nur Rahmi Niatun; Rahman, Rifka Arnita; Rinaldy, Tyara Annisa; Safitri, Hersa; Al Pajar, M. Martin; Ahmad, Islamudin (ANDIL Mulawarman Journal of Community Engagement, 2026)
The “Love Your Country from an Early Age!” program was implemented at SMPN 2 Kota Bangun as a strategic effort to strengthen students’ national awareness in the face of globalization, which often threatens national identity. This community service activity targeted ninth-grade students and student council members, aiming to instill fundamental national values through interactive learning approaches. The methods applied included thematic lectures supported by multimedia presentations, small group discussions, and educational quizzes designed to foster active participation and collaborative learning. Evaluation was conducted using pre-tests, post-tests, and direct observation of student engagement throughout the program. The results demonstrated a significant improvement in students’ understanding of national values. The average pre-test score of 62.5 increased to 84.3 in the post-test, with more than 80% of participants correctly answering basic questions related to Pancasila, the 1945 Constitution, Bhinneka Tunggal Ika, and the Unitary State of the Republic of Indonesia (NKRI). In addition to cognitive gains, students exhibited positive attitudes such as enthusiasm, collaboration, and the ability to connect the material with everyday practices, including respecting diversity and maintaining the school environment. These findings confirm that interactive learning is an effective approach to instilling national values and fostering concrete expressions of patriotism among junior high school students. The program provides a practical model for character education that can be replicated in other schools, thereby contributing to the preservation of Indonesia’s national identity and values in the era of globalization.